2014
DOI: 10.1249/mss.0000000000000351
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Supplementation Enhances the Contractile Properties of Human Skeletal Muscle

Abstract: These results indicate that 7 d of dietary nitrate supplementation enhanced the in vivo contractile properties of the human skeletal muscle. Specifically, nitrate supplementation improved excitation-contraction coupling at low frequencies of stimulation and enhanced evoked explosive force production but did not affect maximum or explosive voluntary force production in untrained individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

28
164
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(205 citation statements)
references
References 31 publications
28
164
0
13
Order By: Relevance
“…These effects, which were reported in predominantly type II muscle, were accompanied by an increased muscle force production. Subsequent studies have confirmed the beneficial effect of NO 3 − on force production in humans (Haider and Folland 2014;Coggan et al 2015). It is therefore possible that elevated type II muscle Ca 2+ handling and muscle contractile function may have further contributed to the improved 1500 m performance observed in the present investigation.…”
Section: Effects Of Brj On 1500 M Tt Performancesupporting
confidence: 70%
“…These effects, which were reported in predominantly type II muscle, were accompanied by an increased muscle force production. Subsequent studies have confirmed the beneficial effect of NO 3 − on force production in humans (Haider and Folland 2014;Coggan et al 2015). It is therefore possible that elevated type II muscle Ca 2+ handling and muscle contractile function may have further contributed to the improved 1500 m performance observed in the present investigation.…”
Section: Effects Of Brj On 1500 M Tt Performancesupporting
confidence: 70%
“…These include, but are not restricted to: lower blood pressure [1][2][3], reduced O2 consumption (V O2) during steady-state exercise [4][5][6], attenuated muscle metabolic perturbations [7,8], and enhanced muscle force production [9,10]. These effects are not directly attributable to the nitrate anion, which is relatively inert [11].…”
Section: Introductionmentioning
confidence: 99%
“…25 The burden of hypertension is particularly important in developing countries where the 26 limited access to adequate treatments and health care and the concomitant occurrence of 27 communicable diseases and nutritional deficiencies increase the risk for disability and 28 cardiovascular fatal events [2].…”
mentioning
confidence: 99%
“…Eight studies had a cross-over study design [7,16, 26]and the remaining five studies adopted a parallel study design [17][18][19]27,28]. Ten studies 129 used a double-blind placebo controlled design [7,16,18,[22][23][24][25][26][27][28]. The trials were conducted characteristics of the studies included in the analysis are presented in Table S1 of the online 133 supplementary material.…”
mentioning
confidence: 99%
See 1 more Smart Citation